Unity of the composite and separation of form in Aristotle - Botter, Barbara (2011)
The main issue of this paper is to study the role form and matter have in sensible substances in Metaphysics Zeta 17 in order to build a general theory of substance which allows for the existence of some non-sensible substances. Although this kind of inquiry must begin with sensible substances, for they are accepted by everyone as substances, it cannot limit itself to their conditions of existence; somehow, it must point to the transcendence of non-sensible substances within the very limits of the form of the substance